Role of Delayed Hypersensitivity in Blastomycosis of Mice - Spencer, Harry D. (1973)
C57BL/6J mice rendered hypersensitive to Blastomyces dermatitidis were protected from the lethal effects of a blastomyces infection. This protection was observed following a lethal intraperitoneal challenge with viable cells 15 days after subcutaneous inoculation with 3.9 × 10(4) viable cells. Delayed hypersensitivity was induced in C57 mice by two injections of Merthiolate-killed cells in adjuvant or by a single injection of viable cells. Development of hypersensitivity was determined at appropriate intervals by footpad injection with killed yeast cells.